A Computer Programming Approach to the Design of Accounting Systems. - Matthews, R. L. (Abacus)
This paper discusses the application of computer technology to the accounting information system. The task of the accounting system is to provide information about economic transactions as a basis for planning, decision-making and control. So far as the input process is concerned, the traditional system is characterized by a multiplicity of data sources, a multi-tiered classification system, a method of recording diverse transactions that has regard to the chronological order in which they occur, and a disaggregated system of ledger accounts which nevertheless reflects the integrating and equilibrating notion of duality of entry. The heterogeneous nature of business transactions and the selective method of recording them in the accounting system will produce an input bottleneck of such proportions as to invalidate the use of the computer unless special action is taken to deal with these problems. Data storage is not inherently a problem in computer applications because of the possibility of utilizing both the computer's own core storage and external media such as punched cards and magnetic tapes. In practice it becomes a problem in relation to accounting operations because of the need for continuous updating of, and ready access to, stored data. The idea of recording accounting data in a matrix system is not a new one. If the accounting system is designed in matrix form, the computer may be programmed to set aside a number of fields corresponding to the cells in the matrix. In the Fortran IV programming language this may be done by means of what is known as a dimension statement.